β-Lactam rearrangements into five-membered heterocycles - Dražić, Tonko; Roje, Marin (Chemistry of heterocyclic compounds, 2017)
Open image in new windowβ-Lactams are compounds of great importance in both medicinal chemistry and as building blocks for the synthesis of different types of biologically relevant compounds. Among other transformations, β-lactams can easily be rearranged into five-membered heterocycles. The rearrangement occurs by cleavage of any of four β-lactam bonds. The type of final five-membered ring mainly depends on the side chain groups of starting β-lactam, as well as reaction conditions. Furthermore, rearrangement reactions are often stereoselective, with product rings retaining the stereochemistry of β-lactams. The ability of β-lactams to form a variety of diversely decorated five-membered heterocycles, often in stereoselective fashion, makes this class of compounds attractive synthons in organic chemistry. This review covers the progress in the field within last ten years.
Gesehen am 29.11.2018